Gene therapy for autoimmune diseases: quo vadis? - Chernajovsky, Yuti (2004)
Biological therapies using antibodies and cytokines are becoming widespread for the treatment of chronic inflammatory autoimmune diseases. However, these treatments have several limitations - such as expense, the need for repeated injections and unwanted side-effects - that can be overcome by genetic delivery. This review summarizes the ingenuity, sophistication and variety of gene-therapy approaches that have been taken in the design of therapeutic molecules and vectors, the engineering of cells and the regulation of gene expression for the targeting of disease outcome. We focus our attention on multiple sclerosis, type 1 diabetes and rheumatoid arthritis.